(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2024)
Abstract. The article deals with the current theoretical and methodological approaches to foming «logistics» category, which is considered as a science and a practical area of business. A retrospective and development evolution of the researched category in military, mathematical and economic aspects is given. Attention is drawn to the fact that in economic science, the genesis of «logistics» category is closely related to forming market relations in industrialized countries. Three main conceptual approaches were studied, which form the definition of the term «logistics» and generally determine the directions of further scientific developments, the nature of logistics use in practice: associativity with material and technical support of production and other types of activities, sales of products; scientific organization of managing infrastructural flow processes by means of their integration, optimization of costs and rationalization of production processes; scientific organization of managing any flow processes in any sphere of human activity. A critical analysis of the considered approaches was carried out from both a scientific and a practical point of view. The differences of F. Kotler’s ideas on market logistics compared to mainstream approaches in the marketing aspect are outlined. The interrelationship of the theory, methodology, object and subject of logistics with certain types of activities, material and goods and related information and financial flows is stated. Attention is focused on the dominant paradigmatic idea – global integration and optimization of flow processes. It is justified that the development of information technologies had the greatest impact on logistics, and logistics itself is now increasingly influencing the development of various spheres of human activity. The genesis of approaches to «logistics» category is summarized: stages, conceptual features and definitions of examined term. It was concluded that in modern conditions, logistics is mainly aimed at increasing the efficiency of integration of any flow processes that have features of spatio-temporal sequence, therefore attempts to globalize logistics fields of application not only in the economy, but also in the science in general, culture, and art etc. are natural.